ACECLOFENAC-INDUCED STEVENS-JOHNSON SYNDROME AFTER ONE SINGLE DOSE: A MAIDEN CASE REPORT - Agarwal, Saurabh; O, Balaji; Patil, Navin (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Drugs are known to cause various adverse drug reactions involving major organ systems. Skin-related adverse reactions are very common and range from a simple rash to life-threatening condition like Stevens-Johnson syndrome. Various drugs are known to cause skin reactions which include antiepileptics, analgesics, antibiotics, and proton-pump inhibitors. Nonsteroidal anti-inflammatory drugs causing life-threatening conditions such as Stevens-Johnson syndrome and toxic epidermal necrolysis are very rare and only few case reports are published. Hence, we report a case of Aceclofenac-induced Stevens-Johnson syndrome after single time administration in a tertiary care hospital in India.